Epidermolysis bullosa: Careful monitoring and no touch principle for anesthesia management - Sujit V Saraf; Nishigandha J Mandawade; Sandeep K Gore; Usha D Padhye; Charissa S Pereira (Wolters Kluwer Medknow Publications, 2013)
Epidermolysis bullosa (EB) is a rare genetic mechanobullous disorder, with excessive fragility of the skin and mucous membranes. Avoiding mechanical injury to the skin and mucous membranes is essential in the anesthetic management. Shearing forces applied to the skin result in bullae formation, while compressive forces to the skin are tolerated. The challenge is to use monitoring technology without damaging the epithelial surface. Difficult airway, positioning issues, nutritional deficiencies, poor immunity, and carcinogenic potential add to the comorbidities. We managed a child with EB undergoing syndactyly release. Ensuring maximal skin and mucous membrane protection, anesthesia in children with EB can be conducted with few sequelae.